W poszukiwaniu prawdy współczesnych nauk humanistycznych. Wytwarzanie wnętrza poprzez projektowanie siebie - Maruszewski, Samuel (Humaniora. Czasopismo Internetowe, 2019)
This article aims to rethink the category of truth in modern humanities. Considering the ever accelerating process of technicisation of culture, human sciences need to readjust and rename the way they influence contemporary society. It is necessary for them to acknowledge the needs of the late post industrial era with all its implications towards philosophical theory. That would mean expanding the spectrum of skills offered by classical humanistic education and remodeling it into the concept of Self design, proposed by the author (Dasein as design). The author draws from the late modernity’s commentators’ and researchers’ critiques in order to diagnose the crisis of the humanities and to develop ideas of his own, that could help to modernize this discipline of knowledge.